2012
DOI: 10.1016/j.jmr.2012.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Cell membrane water exchange effects in prostate DCE-MRI

Abstract: Prostate Dynamic-Contrast-Enhanced (DCE) MRI often exhibits fast and extensive global contrast reagent (CR) extravasation -measured by K trans , a pharmacokinetic parameter proportional to its rate. This implies that the CR concentration ( [CR]) is high in the extracellular, extravascular space (EES) during a large portion of the DCE-MRI study. Since [CR] is detected indirectly, through water proton signal change, the effects of equilibrium transcytolemmal water exchange may be significant in the data and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(84 citation statements)
references
References 28 publications
6
78
0
Order By: Relevance
“…Similarly, some studies have reported that increased metabolic activity is associated with lower τ i (median=0.16–1.03s) in regions of prostrate, 15, 16 and esophageal cancer 17 compared to normal tissues. In yet another study, 18 lower τ i (0.11±0.02s vs. 0.29±0.53s) was observed from normal liver parenchyma (a metabolically more active region) compared to hepatocellular carcinomas.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Similarly, some studies have reported that increased metabolic activity is associated with lower τ i (median=0.16–1.03s) in regions of prostrate, 15, 16 and esophageal cancer 17 compared to normal tissues. In yet another study, 18 lower τ i (0.11±0.02s vs. 0.29±0.53s) was observed from normal liver parenchyma (a metabolically more active region) compared to hepatocellular carcinomas.…”
Section: Discussionmentioning
confidence: 72%
“…12 The unique strength of τ i lies in the fact that it is less sensitive to AIF scaling variations than K trans 13 indicating that τ i is a more reproducible and reliable marker. The parameter τ i has been used to characterize breast, 14 prostate, 15, 16 esophageal 17 and hepatocellular cancer. 18 A recent study 19 also demonstrated the prognostic utility of τ i in predicting survival in patients with hepatocellular carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we used the fast-exchange-regime (FXR)-allowed shutter-speed paradigm model that takes into account this exchange but assumes a single exponential recovery for the 1 H 2 O signal [5,17,18]. This is expressed in R1normaltfalse(normaltfalse)=12[R1normali+r1normalofalse[CRofalse]false(normaltfalse)+R1normalo0+kio+kiovinormalvnormale]  -12{[R1normali-r1normalofalse[CRofalse]false(normaltfalse)-R1normalo0+kio-kiovinormalvnormale]2+(2normalkio)2normalvnormalive}½ where R 1i and R 1o0 are, respectively, the longitudinal relaxation rate constants for the intra- and extracellular 1 H 2 O signals (in the absence of exchange and CR); r 1o is the interstitial CR relaxivity; k io is the unidirectional equilibrium cellular water efflux rate constant (reciprocal of the mean intracellular water lifetime, τ i ); and v i and v e are the respective intra- and extracellular volume fractions.…”
Section: Methodsmentioning
confidence: 99%
“…This is usually an incorrect over-simplification. The direct consequences of using tracer paradigm (TP) models are systematic errors in the estimated pharmacokinetic parameters such as K trans [example below] and v e [13,57]. Nevertheless, since tracer models find common use in the literature because of their relative simplicity, we also used one, the standard, fast-exchange-limit (FXL)-constrained Tofts tracer model [22], in addition to the FXR-SSP model in assessing the effects of AIF scaling uncertainty.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation